1994
DOI: 10.1002/j.1550-8528.1994.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response to Exercise with Constant Energy Intake in Identical Twins

Abstract: Seven pairs of young adult male identical twins completed a negative energy balance protocol during which they exercised on cycle ergometers twice a day, 9 out of 10 days, over a period of 93 days while being kept on a constant daily energy and nutrient intake. The total energy deficit caused by exercise above tlie estimated energy cost of body weight maintenance readied 244 f 9.8 MJ (Mean f SEM).Baseline energy intake was estimated over a period of 17 days preceding the negative energy balance protocol. M e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0
10

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(191 citation statements)
references
References 16 publications
3
178
0
10
Order By: Relevance
“…Several studies have shown that FM, FFM and AVF in sedentary people are partly under genetic control. 7 ± 9 Moreover, identical twin intervention studies showed that the intrapair variation in responsiveness was signi®cantly smaller than the interpair variation, 6,10 suggesting that the changes in FFM, FM, %FAT and AVF are also partly determined by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that FM, FFM and AVF in sedentary people are partly under genetic control. 7 ± 9 Moreover, identical twin intervention studies showed that the intrapair variation in responsiveness was signi®cantly smaller than the interpair variation, 6,10 suggesting that the changes in FFM, FM, %FAT and AVF are also partly determined by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Aerobic exercise training can alter FM, FFM and AVF in humans, 3,4 and large individual differences in response have been reported. 5,6 Sex, age and pretraining level may explain some of these differences. That FM and FFM levels are partly under genetic control was shown in the Que Âbec Family Study with twins, adopted siblings and nuclear families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ®rst study utilized overfeeding to cause weight gain in male identical twins of normal weight; 10 the second utilized exercise to cause weight loss in male identical twins with modestly elevated weight. 11 These studies 10,11 as well as postoverfeeding results 12 suggested a genetic contribution to the regulation of body weight, body fat and their determinants. Thus, there was a great similarity in changes in these variables within twin pairs despite large differences among twin pairs.…”
Section: Introductionmentioning
confidence: 96%
“…Three intervention studies performed with pairs of identical twins confirmed that there was a latent and most likely inherited predisposition to gain Progress in obesity research C Bouchard adipose tissue and weight when exposed to a standard amount of excess energy 15 or to lose fat mass and weight when exposed to negative energy balance conditions. 16,17 The focus of research evolved rapidly to an emphasis on candidate genes, positional candidates, single-gene disorders, quantitative trait loci from genomic scans and DNA polymorphisms. There was intense cross talk between rodent genetic models and human clinical cases, particularly when it came to single-gene defects.…”
Section: Geneticsmentioning
confidence: 99%